"The Harder One Tries …": Findings and Insights From the Application of Covert Response Pressure Assessment Technology in Three Studies of Visual Perception. (April 2020) - Tsikandilakis, Myron; Bali, Persefoni; Haralabopoulos, Giannis; Derrfuss, Jan; Chapman, Peter
In this article, we present a force measuring method for assessing participant responses in studies of visual perception. We present a device disguised as a mouse pad and designed to measure mouse-click-pressure and click-press-to-release-time responses by unaware, as regards to the physiological assessment, participants. The aim of the current technology, in the current studies, was to provide a physiological assessment of confidence and task difficulty. We tested the device in three experiments. The studies comprised of a gender-recognition study using morphed male and female faces, a visual suppression study using backwards masking, and a target-search study that included deciding whether a letter was repeated in a subsequently presented letter string. Across all studies, higher task difficulty was associated with higher click-release-time responses. Higher task difficulty was, intriguingly, also associated with lower click pressure. Higher confidence ratings were consistently associated with higher click pressure and shorter click-release time across all experiments. These findings suggest that the current technology can be used to assess responses relating to task difficulty and participant confidence in studies of visual perception. We suggest that the assessment of release times can also be implemented using standard equipment, and we provide manual and easy-to-use code for the implementation.